Usury in the Heavenly Religions: A Comparative Study between the Holy Qur’an, the Gospel, and the Torah - Adel Nashaat Al-Hasani (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Usury remains a central issue in religious ethics and economic discourse, particularly within Islam, Judaism, and Christianity. Specific Background Each of these Abrahamic religions addresses usury through its sacred texts, offering distinct yet related perspectives on financial justice and social responsibility. Knowledge Gap Despite existing studies, there is limited integrated analysis that compares these perspectives while linking them to broader moral and economic implications. Aims This study aims to analyze and compare the concept, prohibition, and implications of usury across the Qur’an, the Torah, and the Gospel. Results The findings reveal a shared ethical rejection of exploitative financial practices, with Islam presenting a strict and categorical prohibition, Judaism allowing conditional application within specific social boundaries, and Christianity emphasizing moral values such as compassion and generosity rather than formal legal prohibition. Novelty The study provides a structured comparative synthesis of textual, theological, and ethical dimensions of usury across the three religions. Implications These findings contribute to understanding how religious principles can inform contemporary discussions on economic justice and ethical financial systems. Highlights• Comparative interpretation reveals shared ethical rejection of financial exploitation• Distinct legal and moral frameworks identified across three religious traditions• Textual analysis connects religious teachings with socio-economic considerations KeywordsUsury; Comparative Religion; Abrahamic Traditions; Religious Ethics; Economic Justice